Women and Extractivism in Kaine Agary’s Yellow-Yellow: A Postcolonial Ecofeminist Critique - Gebrehiwot, Dagnachew Adefris (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This article aims to examine the exploitation of women in Kaine Agary’s novel Yellow-Yellow (2006). The novel has been analyzed from a postcolonial ecofeminist perspective. The postcolonial ecofeminist analysis of this novel reveals the exploitative type of relationship between women and extractivism, which can manifest the destruction of nature through the over-extraction of crude oil by transnational corporations. In this manner, Bibaebi, the major female character, is oppressed by the oil extraction process, dispossessed of her farmland, and faced with displacement and illicit migration. The study also reveals that though women are the brunt of persistent oppression, women’s interconnectedness to nature is a pathway to survival and resilience. Bibaebi and her daughter, Zilayefa, form a core of resistance against the petro-capitalist exploitation of nature. Ultimately, this study situates women within the broader discourse of neocolonial extractivism, underscoring the pressing need to reevaluate the intersection of women and nature in contemporary African literature.